Growth Performance of Mirror Carp (Cyprinus carpio var. specularis, Lacepède, 1803) Fry Fed with Varying Protein Content Feeds - Rahman, S.M.; Shahin, M.A.A.; Chisty, M.A.H.; Rahman, M.M.; Tareque, A.M.H.B.; Hasan, M.M. (Our Nature, 2013)
An experiment was conducted in aquaria for seven weeks to examine the effect of varying dietary protein level on growth, FCR (food conversion ratio) and survival of mirror carp fry. Similar weight (2.29 ± 0.08g) and length (4.21 ± 0.05 cm) of mirror carp fry were stocked in the aquaria (1 fry/L) and fed laboratory prepared feeds containing 25% (T1), 30% (T2), 35% (T3), 40% (T4), and 45% (T5) protein. In terms of growth and FCR, diet containing 30% protein performed significantly (p<0.01) better than those of other tested diets. Survival rate, on the other hand, dropped significantly (p<0.01) when the stocks were fed diets containing over 30% protein. These findings suggest that about 30% protein in diet appears to be sufficient for obtaining optimum growth of mirror carp fry. DOI: http://dx.doi.org/10.3126/on.v10i1.7747